LEGAL PROTECTION FOR CHILDREN AS VICTIMS OF VERBAL SEXUAL HARASSMENT IN PUBLIC SPACES (CASE STUDY OF HARAPAN SATU PRIVATE HIGH SCHOOL, MEDAN) - Muhammad Ragil Rayhan; Atikah Rahmi (Inspiring Law Journal, 2026)
This thesis discusses legal protection for child victims of verbal sexual harassment in public spaces. Verbal sexual harassment, also known as catcalling, is a common occurrence in public spaces, especially in Indonesia. While public spaces should be a safe place, the behavior is not directly proportional to this. This behavior not only makes children feel unsafe and uncomfortable, but can also cause psychological trauma under Indonesian criminal law and legal protection for victims of verbal sexual harassment (catcalling). The legal umbrella that is expected to provide justice and protection for victims is, in fact, ignored in the slightest. Victims are left to suffer from all the impacts of the sexual harassment they receive, while perpetrators are allowed to roam free without being given the sanctions they deserve. This study aims to find out the forms of verbal sexual harassment in public spaces, legal protection for child victims of verbal sexual harassment in public spaces, and prevention efforts for child victims of verbal sexual harassment in public spaces. The research method used in this study is empirical legal research. The data sources are Islamic legal sources, primary data, and secondary data. The research location is Jalan Imam Bonjol No. 35. The data collection tool is a questionnaire/survey. This research was conducted at Harapan Satu Private High School, Medan. Forms of verbal sexual harassment in public spaces include inappropriate comments about physical appearance, whistling, and teasing. Protection for victims of verbal sexual harassment in public spaces is provided in Article 5 of the TPKS Law, which carries a maximum prison sentence of 9 (nine) months and/or a maximum fine of Rp. 10,000,000.00 (ten million rupiah). Prevention of verbal sexual harassment can be done holistically through education, outreach, and the implementation of firm policies.